Level of Satisfaction, Motivation, Teacher Profession and Providing Financial Compensation in Improving Teacher Performance (Survey Conducted on Private High School Teachers in Tangerang City, Banten Province) - Sugandha Sugandha; Suhendar Janamarta; Fidellis Wato Tholok (Fakultas Bisnis, 2022)
in this study aims to determine how big the relationship between satisfaction, motivation, the teaching profession and the provision of financial compensation partially or simultaneously on performance. The method of data collection is by distributing questionnaires to private school teachers in Tangerang City directly. The t-test shows that the magnitude of the Satisfaction Variable (X1) has a positive and significant effect (t-count Satisfaction 1.977. > ttable 1.65 and .0049 <0.05 on Performance, Motivation Variable (X2) has a positive and significant effect (t value of motivation 3519 > t table 1.65 and 0.0001 <0.05 on performance, the variable of the teaching profession (X3) has a positive and significant effect (the t-count value of the teaching profession is 3.664. > t-count) tables 1.65 and .0000 <0.05 the financial compensation performance variable (X4) has a positive and significant effect (t value 9.748 > t table 1.65 and 0.00000 <0.05 on performance and for the F test results, the results for the calculated F value are 94,925 with a significance value of 0.000 so that the calculated F value > F table or 94.925 > 3.87 or the significance level (sig) 0.000 <0.05, it can be concluded that there is a simultaneous influence between ionic satisfaction, motivation, the teaching profession and the competence of providing financial satisfaction on performance and the value of R2 y